Local Government Financial Performance with a Value For Money Approach: Evidence from Jayapura Indonesia - Rasyid, Abdul (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The objective of this study is to evaluate the financial performance of the Jayapura City Education and Culture Office through the utilization of the Value for Money approach, which has three primary components: economy, efficiency, and effectiveness. This study is a descriptive research conducted to examine the financial performance of programs and activities within the Jayapura City Education and Culture Office. The study specifically focuses on analyzing the budget targets and actual outcomes as reported in the Jayapura City Education and Culture Office's Government Agency Performance Accountability Report (LAKIP) for the periods of 2019 and 2020. The employed methodology for data analysis is quantitative descriptive analysis, which aims to assess several dimensions of economy, efficiency, and effectiveness. The present analysis is based on research findings about the performance of the Jayapura City Education and Culture Office in three specific programs. These programs include the Nine-Year Compulsory Education Program, the Improvement Program for the Development of Performance and Financial Reporting Systems, and the Procurement, Improvement, and Repair of Educational Facilities and Infrastructure Program. The findings of this study offer a comprehensive analysis of the financial performance of the Jayapura City Education and Culture Office, thereby serving as a valuable point of reference for enhancing and advancing future projects.